A great and downward hunt: How to design inorganic trauma. (1st December 2016) - Woodard, Ben
While many of the physical sciences have historically and conceptually informed philosophy, geology is one field that has not received adequate philosophical attention. In what follows, I attempt to demonstrate how the relation between the geological and the philosophical is over-coded in numerous historical and fictional contexts in the form of geotrauma, the violence of the earth or the inorganic on the organic, and the violence of the inorganic on itself. Historico-mythical tales of the violence of mining and surveying often centre on the geological landscape as offering a form of violence, or as invading the consciousnesses of those around it with a form of ancient violence. In this regard, the earth's geological forces can be treated as murderous agents, where investigating the crime simply seems to redouble the violence. The article examines how this strange and violent reflectivity deploys itself in an exaggerated way in weird and gothic fiction. Looking at the works of Fritz Leiber, H. P. Lovecraft and Charles Brockden Brown, this article attempts to argue how the fictionalization of geotrauma is a dramatization of the already existent co-implication of geology and philosophy in the form of a co-murdering and the traumatic nature of the expansive concept.